2020
DOI: 10.12688/f1000research.23775.2
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Non-microscopic surgical management of incomplete penile amputation

Abstract: Background: Penile amputation is an emergency urologic condition requiring immediate attention in order to maximize functional outcomes. Unfortunately, there is limited experience and publication of case reports describing the successful replantation of penis after incomplete amputation, especially in facilities without adequate microsurgical tools and means. We hereby present a case of penile amputation caused by a mechanical grass cutter and a discussion of its surgical management. Case description: A 33-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…Similar to the reports mentioned earlier, adequate deep and superficial arterial blood flow was revealed at the distal end of the penis. [20] In contrast to the clinically desirable findings reported by this study, a year earlier, in 2019, Elmaraghi et. al.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Similar to the reports mentioned earlier, adequate deep and superficial arterial blood flow was revealed at the distal end of the penis. [20] In contrast to the clinically desirable findings reported by this study, a year earlier, in 2019, Elmaraghi et. al.…”
Section: Discussioncontrasting
confidence: 82%
“…All of the included studies were case reports of penile amputation with different causes, including assaults [15][16][17], accidents [18][19][20], circumcision complication [21], or self-mutilation induced by drugs [4] and psychosis episodes. [22][23][24][25] One study reported self-amputation in a male patient without mentioning the underlying cause.…”
Section: Studies Included In Quantitative Synthesismentioning
confidence: 99%
“…In situations of penile glans amputation or when instrumentation for microscopic surgery is not available, macroscopic replantation may be another reconstructive option to salvage the amputated penis [2] [12]. The first two patients presented had macroscopic replantation of the amputated glans and the penis with a favorable outcome with regards to voiding function and sensation during 8 months period of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Penile stump replantation without repair of dorsal vessels of the penis could be considered as a graft. Thus the replanted graft will survive by imbibition by obtaining nutrients from the adjacent graft by diffusion [12]. The penile graft is successful because the dorsal and urethral arteries serve as an excellent source of blood supply to the corpus spongiosum and the glans.…”
Section: Discussionmentioning
confidence: 99%